2020
DOI: 10.3390/vaccines8020204
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Sclerosis and Vaccinations: A Register-Based Cohort Study about Seasonal Influenza and Streptococcus pneumoniae Vaccination Rate and Uptake from Liguria Regional Center, Northwest Italy

Abstract: Systemic sclerosis (SSc) is the connective tissue disease with the highest mortality and patients with chronic inflammatory immune-mediated diseases are at high risk of acquiring infections as they are often treated with immunosuppressive or biological drugs. This study, conducted among the patients followed by our clinical immunology, part of the Internal Medicine Department in the Ospedale Policlinico San Martino, Genoa, northwest Italy, has set itself the primary objective of analyzing the vaccine uptake an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Among hospitalized patients with influenza, those younger than 5 years old and older than 65 years old are more likely to develop acute pneumonia [ 119 , 120 , 121 , 122 ]. Therefore, it is more important for people younger than 5 years old and older than 65 years old to be vaccinated against influenza [ 123 ]. The immune response of young individuals may be more vigorous, and it is easy to trigger a stronger cytokine storm.…”
Section: Biological Factorsmentioning
confidence: 99%
“…Among hospitalized patients with influenza, those younger than 5 years old and older than 65 years old are more likely to develop acute pneumonia [ 119 , 120 , 121 , 122 ]. Therefore, it is more important for people younger than 5 years old and older than 65 years old to be vaccinated against influenza [ 123 ]. The immune response of young individuals may be more vigorous, and it is easy to trigger a stronger cytokine storm.…”
Section: Biological Factorsmentioning
confidence: 99%
“…A few of these studies investigated the rate of vaccination also in relation to gender [14,26,[28][29][30][31]34,37], age [14,[26][27][28]30,31,34,37], concomitant medical therapies [14,[28][29][30]37], disease duration and comorbidities [26,30,31,37], referral by a physician, indication for vaccination, educational levels [14,37] and knowledge attitude towards vaccination [14,27,29,31,34], vaccination settings such as rural vs. urban [14] and concomitant vaccination campaigns aimed to improve the vaccination rate [26,32,33,35], however these outcomes were variably reported.…”
Section: Vaccine Coverage Ratementioning
confidence: 99%
“…Some of the studies found through the systematic review on the vaccine coverage also investigated reasons for low rates and possible improvement strategies. For what concern the factors mainly affecting the vaccination uptake, there were the older age, the recommendation by physicians, and biological therapy [14,[26][27][28][29][30][31]34,37]. Also, awareness and favorable attitude toward vaccination was a positive predictor for vaccination, but not the level of education [14,27,29,31,34].…”
Section: Improving Vaccine Coverage In Autoimmune Patients and In Ssc Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary manifestations are known to occur in all autoimmune diseases that have standardized incidence ratios greater than 2.0, indicating that autoimmune process can lead to lung cancer susceptibility [ 8 ]. Systemic sclerosis is one of the connective tissue diseases with the highest mortality rate [ 11 , 22 ], and it has recently been reported that patients with systemic sclerosis have an increased risk of lung cancer [ 23 , 24 ], but the intrinsic gene connection is unclear. Our results reveal that genes related to innate immune response and response to virus were co-upregulated significantly in patients with systemic sclerosis and lung cancer.…”
Section: Discussionmentioning
confidence: 99%